Prevalence of thrombocytopenia in neonates admitted in NICU with culture proven sepsis - Singh, Shivraj; Agrawal, Avyact; Mohan, Uthara; Awasthi, Sukarn (International Journal of Contemporary Pediatrics, 2018)
Background: Thrombocytopenia is a common haematological problem encountered during neonatal period, particularly in the sick, premature neonates admitted in the NICU, and usually indicate an underlying disease process. Thrombocytopenia may be considered as an important and early tool in diagnosis of septicaemia in neonates. Methods: It is a hospital based cross sectional study. A total 105 neonates with blood and/CSF culture positive sepsis and associated thrombocytopenia admitted in NICU. This study was conducted to find the prevalence of thrombocytopenia in neonates admitted in NICU with culture proven sepsis and to observe the outcome of thrombocytopenia and sepsis. Results: Out of 105 culture positive neonates K. pneumoniae 47/105 (44.8%) was the commonest micro-organism isolated, followed by Pseudomonas 26/105 (24.8%), E. coli 14/105 (13.3%), Staphylococcus 11/105 (10.5%), Candida 2/105 (1.9%) in decreasing order. Thrombocytopenia was present in 100/105 (95.2%). Among thrombocytopenic neonates 38/100 (38%), 36/100 (36%) and 26/100 (26%) having severe, moderate and mild thrombocytopenia respectively. 38 (38%) newborns of severe thrombocytopenia among them K. pneumoniae (50.0%) was commonest organism, followed by Pseudomonas. (23.7%) and Staphylococcus (15.8%) in the decreasing order. 36 (36%) newborns of moderate thrombocytopenia among them K. pneumoniae (47.2%) again commonest organism associated, followed by Pseudomonas. (25.0%), and E- coli (11.1%). In severe thrombocytopenic newborns both GI and pulmonary (60.50%) haemorrhage was the most common bleeding manifestation. Mortality rate (37.1%) was high in newborns having sepsis. Conclusions: Bacterial sepsis is significantly complicated by thrombocytopenia. Severe thrombocytopenia in a suspected case of bacterial sepsis might predict Klebsiella sepsis and hence it may be rational to start empirical antibiotics covering the same.